POTENSI RITEL PANGAN BERBASIS PERDAGANGAN DIGITAL DENGAN MEMAHAMI PERILAKU KONSUMEN: PERSPEKTIF PELAKU AGRIBISNIS - Utami, Hesty Nurul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Technology development applied to the retail food business, and more consumers accept the online shopping modes for daily needs become some of the factors supporting the development of digitally based food retail. However, the development of the digitally based food retail industry in Indonesia could be considered as still in an early development stage of digitalization. This requires further understanding of the market and marketing potential based on understanding consumer behaviour to see the opportunity for developing digital-based food retail. This research aims to explore the knowledge of the agribusiness actors involved in digitally based food retail about consumer behaviour that has potential for business and marketing development, specifically the small and medium scale businesses. An inductive approach was applied for this research using in-depth interviews with agribusiness actors in West Java and Jakarta that use the digital retail channel for the business. The study found consumer behaviour that can potentially support food retail with digital-based in Indonesia is related to social, cultural, and consumer habitual aspects. These factors comprise the changes in consumer shopping habits, cooking and food consumption habits, food-related lifestyle, communication and interaction modes, the potential of women and urban consumers, and the increasing trend of healthy food consumption. This research contributes to consumer behaviour for food shopping through online channels, and digitally based food retail transformation, and practically for agribusiness actors on developing strategic and effective marketing for promoting food products in this digital era.